Functional and historical determinants of shape in the scapula of Xenarthran mammals: Evolution of a complex morphological structure - Monteiro, L. R.; Abe, Augusto Shinya [UNESP] (Wiley-Blackwell, 1999)
The mammalian scapula is a complex morphological structure, composed of two ossification plates that fuse into a single structure. Most studies on morphological differentiation in the scapula have considered it to be a simple, spatially integrated structure, primarily influenced by the important locomotor function presented by this element. We used recently developed geometric morphometric techniques to test and quantify functional and phylogenetic influences on scapular shape variation in fossil and extant xenarthran mammals. The order Xenarthra is well represented in the fossil record and presents a stable phylogenetic hypothesis for its genealogical history. In addition, its species present a large variety of locomotor habits. Our results show that approximately half of the shape variation in the scapula is due to phylogenetic heritage. This is contrary to the view that the scapula is influenced only by functional demands. There are large-scale shape transformations that provide biomechanical adaptation for the several habits (arboreality, terrestriality, and digging), and small scale-shape transformations (mostly related to the coracoid process) that are not influenced by function. A nonlinear relationship between morphometric and phylogenetic distances indicates the presence of a complex mixture of evolutionary processes acting on shape differentiation of the scapula. J. Morphol. 241,251-263, 1999. (C) 1999 Wiley-Liss, Inc.
Keywords: geometrics morphometrics; scapula; Xenarthra; comparative methods; thin plate spline